An investigation of the risk factors of chronic obstructive pulmonary disease in natural population-based cohorts in China – a nested case-control study - Xu, Yixin; Zhao, Hongjun; Yu, Chunchun; Wang, Yuqian; Xu, Hao; Weng, Zhe; Chen, Chengshui; Mao, Haizhou (Frontiers in Public Health, 2023)
Background: Chronic obstructive pulmonary disease (COPD) has become one of the most significant chronic diseases in China. According to conventional wisdom, smoking is the pathogenic factor. However, current research indicates that the pathophysiology of COPD may be associated with prior respiratory system events (e.g., childhood hospitalization for pneumonia, chronic bronchitis) and environmental exposure (e.g., dust from workplace, indoor combustion particles). Dyspnea, persistent wheezing, and other respiratory symptoms further point to the need for pulmonary function tests in this population. Reducing the burden of chronic diseases in China requires a thorough understanding of the various factors that influence the occurrence of COPD.Methods: Using a cohort from the natural population, this study used nested case-control analysis. We carried out a number of researches, including questionnaire surveys and pulmonary function testing, in the Northwest and Southeast cohorts of China between 2014 and 2021. After removing any variations in the baseline data between patients and control subjects using propensity score matching analysis, the risk factors were examined using univariate or multivariate regression.Result: It was discovered that prior history of chronic bronchitis, long-term wheezing symptoms, and environmental exposure-including smoking and biofuel combustion-were risk factors for COPD. Dyspnea, symptoms of mobility limitation, organic matter, and a history of hospitalization for This is a provisional file, not the final typeset article pneumonia at an early age were not significant in the clinical model but their incidence in COPD group is higher than that in healthy population.Discussion: COPD screening effectiveness can be increased by looking for individuals with chronic respiratory symptoms. Smokers should give up as soon as they can, and families that have been exposed to biofuels for a long time should convert to clean energy or upgrade their ventilation. Individuals who have previously been diagnosed with emphysema and chronic bronchitis ought to be extra mindful of the prevention or advancement of COPD.